Psycho-Historical Contextualization for Music and Visual Works: A Literature Review and Comparison Between Artistic Mediums - Chmiel, Anthony; Schubert, Emery (Frontiers in Psychology, 2019)
A significant contribution to the literature on aesthetics in the last decade has been Bullot and Reber’s ecologically-driven psycho-historical framework for the science of art appreciation (PHF). The framework proposes that the presence of contextualizing information accompanying an artwork will impart a substantial impact on appreciation for it, which is accessible through understanding of the causal information surrounding the work. Artistic understanding is outlined in terms of three hierarchical ‘modes’ of appreciation. This paper tested a simplified hypothesis drawn from the PHF, using results reported in the existing literature. As Bullot and Reber note that such a framework is relevant for any artistic medium containing causal information, results were drawn from literature concerned with either music or visual works. Our review identified 34 studies that reported results of appreciation (or equivalent) as a dependent variable, while manipulating contextual/historical information for the stimuli as an independent variable. Overall the results were consistent across the two artistic mediums: 9 experiments (26%) produced strong support for the PHF, 6 experiments (18%) produced inconclusive results, and 19 experiments (56%) produced no support for the PHF. We conclude that the majority of the reviewed literature does not support the simplified PHF hypothesis for either medium. However, we also discuss a number of limitations surrounding these studies which may have produced a substantial impact on the categorization results: small sample sizes in some studies; difficulty in translating philosophically-based theory into empirical practice, and interactions with variables such as exposure and ‘unusualness’.